Researcher, coach developer, and coaches' perspectives on learner-centered teaching in a rugby coach education program - Ciampolini, V.; Camiré, M.; das Neves Salles, W.; do Nascimento, J. V.; Milistetd, M. (International Sport Coaching Journal, 2022)
In the sports coaching field, learner-centered teaching (LCT) has been advocated as a viable approach to increasing learners` involvement in the learning process. However, implementing LCT is not a simple undertaking as coach developers, and coaches have encountered dilemmas when it comes to shifting to LCT in coach education. This study aimed to investigate how LCT principles were implemented in a rugby coach education program through the perspectives of the researcher, the coach developer, and coaches. Participants included the researcher (i.e., first author), a coach developer, and 10 rugby coaches. The researcher observed three coach education courses, gathered descriptive and reflective field notes, and conducted individual semistructured interviews with both the coach developer and the 10 coaches. Findings shed light on the strategies adopted by the coach developer and the extent to which these strategies aligned with LCT principles. Coaches discussed how they enjoyed their active role in the courses and the approaches used by the coach developer to leverage learning. The discussion highlights the importance of coach developers in facilitating a learning process that is challenging, motivating, and supports coaches throughout the courses.